Psychiatric disorders associated with fluoroquinolones: a pharmacovigilance analysis of the FDA adverse event reporting system database - Xie, Wen-Long; Ge, Meng-Lan; Chen, Dan; Chen, Guo-Qing; Mei, Yuan-Xi; Lai, Yong-Ji (Frontiers in Pharmacology, 2024)
Background: Fluoroquinolones are broad-spectrum antibiotics with significant antimicrobial activity.Despite their therapeutic benefits, they are associated with a range of adverse drug reactions (ADRs), particularly those affecting the central nervous system (CNS). This study aimed to analyze the psychiatric ADRs linked to fluoroquinolones using data from the FDA Adverse Event Reporting System (FAERS) database.Methods: A retrospective pharmacovigilance study was conducted using FAERS data from Q1 2004 to Q4 2023. The data processing phase involved the FDA-recommended deduplication method, and ADRs were classified according to Medical Dictionary for Regulatory Activities (MedDRA).Disproportionality analysis was performed using the reporting odds ratio (ROR), and statistical significance was assessed using the Chi-square test or Fisher's exact test.The study identified 84,777 reports associated with fluoroquinolones, with 359,480 Preferred Terms-annotated entries, 27816 of these reports were psychiatric ADRs. mood disorders were the most frequently reported, including anxiety, depression, and delirium, with some reports escalating to suicidal ideation and behaviors. The Standardized MedDRA Query classification system was used to categorize these ADRs into Depression, Suicide/self-injury, Psychosis and psychotic disorders, and Non-infectious encephalopathy/delirium. Ciprofloxacin was most frequently linked to depression and suicidal ideation, while moxifloxacin showed a robust correlation with delirium. The risk of psychiatric ADRs varied by age group, with affective disorders more prevalent in adults under 65 and psychosis and delirium in those over 65.Fluoroquinolones are associated with a range of psychiatric ADRs, with notable differences between the drugs in the class. The study highlights the need for caution in prescribing fluoroquinolones, particularly for patients with pre-existing mental health conditions or those in higher risk age groups. The findings also underscore the importance of considering age-specific preventive strategies when administering these antibiotics.